Resilience-promoting factors for parents of severely injured children during the acute hospitalisation period: A qualitative inquiry. Issue 5 (May 2019) - Foster, Kim; Mitchell, Rebecca; Young, Alexandra; Van, Connie; Curtis, Kate
Highlights: Many parents experience stress and anxiety following paediatric injury. A range of resilience-promoting factors facilitate parental wellbeing during the initial post-injury period. Resilience-promoting factors for parents can be used to inform brief online intervention modules to enhance parent resilience. Abstract: Background: Paediatric injury impacts the entire family. Many parents experience stress and anxiety following paediatric injury, but little is known about factors that support parents' wellbeing and how they successfully manage the adversity of child injury during acute hospitalisation. Aim: To explore parent experiences and resilience-promoting factors that facilitate the wellbeing of parents with severely injured children during the acute hospitalisation period. Methods: A qualitative inquiry conducted across four major Australian paediatric trauma services. Semi-structured interviews were conducted with a purposive sample of 40 parents of 30 severely injured children aged 0–12 years during the acute post-injury hospitalisation period. Interviews explored parents' experiences and how parents had managed the stress of their child's injury during the acute hospitalisation period. Data were analysed using directed content analysis. Results: Parents identified a range of individual characteristics and resources, and those of their children and families, communities, and the hospital environment, which facilitated their wellbeing during the initial post-injury period. Three themes were derived from analysis: Drawing on inner strengths; Having positive and supportive relationships; Being in a safe place with the right help. Conclusion: Resilience-promoting factors for parents of injured children can be used to inform development of brief online intervention modules to enhance parent resilience. Routine screening and targeted psychological first aid for parental distress are recommended.